Designing a Building for Shadow Puppet Shows in Semarang City - David Herlambang; Yuke Ardhiati (Journal of Aesthetics, Creativity and Art Management, 2023)
The study aim is how to create a different building design that is able to attract the interest of young people who are able to accommodate and also preserve the art of Shadow Puppet (shadow puppet) that it is known by the wider community. Based on the shortage of shadow puppet show facilities in Semarang as the capital of Central Java, the procurement of a shadow puppet performance facility which has educational facilities for the Dalang or puppeteer profession is felt to be the right solution to preserve and revive this art of Shadow Puppet. The design of the shadow puppet show building in Semarang City raises the philosophy of the mountains of Shadow Puppet called “Kayon". Harmony with Nature as the architectural theme of the shadow puppet performance building was chosen so that the architecture of the building can live in harmony with nature by understanding and accepting the inanimate reality of natural forces.